Formulation and Evaluation of Hydrogel containing Bauhinia Racemosa - R. Hangargekar, Sachin; N. Nagoba, Shivappa; Hashmi, Aakif S.; Shaikh, Atiya (Journal of Neonatal Surgery, 2025)
Hydrogels are three-dimensional networks made up of hydrophilic polymer links that are cross-linked chemically or mechanically. In order to speed up the healing process, it designates insoluble hydrophilic structures that have the capacity to absorb wound exudates and permit oxygen diffusion. The aim of present study is to formulate and evaluate hydrogel containing Bauhinia racemosa. For cure of wound healing number of synthetic drugs are obtainable but herbal remedies offer a promising alternative to synthetic drugs due to their biocompatibility, affordability, and low toxicity. A preliminary phytochemical study of Bauhinia Racemosa extract showed the presence of flavonoids and polyphenols both of which aid in wound healing and skin tissue regeneration. The F1-F7 formulations of Bauhinia Racemosa hydrogel for wound healing was formulated using different concentration Carbopol-940 (0.5-2%) and evaluated for appearance pH, Viscosity, Spreadability, Drug content, In-vitro drug diffusion and Stability studies. In those seven formulations the F5 shows better results as compare to other batches i.e. pH-5.6, Viscosity-9000 cps, Spreadability-6.9 cm, Drug content-83 % and good percentage of drug diffusionstudy i.e. 86.11%. ICH Q1A (R2) conditions for stability study over 3 months confirmed the formulation's stability with no major changes in appearance, pH, and drug content & in vitro drug diffusion. Appropriate selection of polymer and their proportions is a prerequisite for designing and developing a hydrogel. The prepared hydrogel showed better results for homogeneity, drug release rates & good stability when compared to marketed formulation.